Contribution of CRP to Illinois Bobwhite Habitat at the Landscape Level (Poster Abstract) - Whitney L. Weber; John L. Roseberry (National Quail Symposium Proceedings, 2017)
Northern bobwhite (Colinus virginianus) population declines in the midwest have been attributed to habitat degradation and loss due mainly to intensified agricultural land use and farming practices. Thus, there was initial optimism that the Conservation Reserve Program (CRP) would benefit bobwhites by converting cropland to semi-permanent grassland. However, CRP apparently has not positively impacted regional or statewide population trends in Illinois. Deficiencies at both site and landscape level may be involved. To address the latter issue, we mapped the location of each individual CRP field (> 8,800) in 11 representative counties within the bobwhite range in Illinois. We then analyzed their spatial relationship to other land cover and bobwhite habitat using Geographic Information Systems and a statewide digital land cover map based on classified satellite imagery. Existing bobwhite habitat and CRP fields tended to be spatially correlated because both are largely confined to moderately rolling terrain as opposed to very hilly or very flat areas. Nevertheless, almost 25% of all existing CRP acreage within our 11 study counties occurred in landscapes with insufficient woody edge to support high bobwhite populations. Furthermore, CRP did not always provide the habitat component most limiting for bobwhites.